Dietary Intake and Performance Status of Hospitalized Cancer Patients on Different Treatment Modalities - Usharani, K.; Vijayalakshmi,; Roy, R. K.; Prakash, Jamuna (The Indian Journal of Nutrition and Dietetics, 2005)
Cancer in simple terms is an uncontrolled growth of cells. These are cells that have acquired ability to multiply and spread without restriction. Any cell tissue or organ in the body can be affected. Cancer is a set of disease states rather than a single disease with devastating impacts in terms of mortality as well as physical and psychological morbidity. The growth of a tumour leads to profound alterations of body organs and functions. As a result of this a poorly understood syndrome, "cachexia" develops. Cancer patients frequently lose body weight and anorexia is one of the prime determinants of weight loss. Pre-treatment weight loss is associated with decreased median survival and response to therapy. The three types of therapy used in the treatment of cancer are surgery, radiotherapy and chemotherapy.